SAT0097 Factors associated with atherosclerosis progression in patients with low-active rheumatoid arthritis. (15th June 2017) - Giollo, A; Dalbeni, A; Tagetti, A; Atanasio, S; Orsolini, G; Cioffi, G; Ognibeni, F; Rossini, M; Fava, C; Viapiana, O
Abstract : Background: Longitudinal studies of the carotid intima-media thickness (IMT) change in RA suggested a role for inflammation in atherosclerosis progression. However, data on well controlled joint disease are scarce since most studies enrolled patients with very high disease activity. Objectives: To estimate atherosclerosis progression and identify influencing factors in a cohort of longstanding and well controlled RA patients. Methods: One hundred nine RA patients (females 80%, age 59±12 years, disease duration 15.6±10.6 years, mean Framingham 10-year CV disease risk score 16±12%) without previous cardiovascular (CV) events underwent carotid ultrasound (CUS) examination at baseline and after a mean time of 1.1±0.3 years. Atheromatous plaques and intima-media thickness (IMT) were assessed. Data on CV risk factors, inflammation markers, medications, and RA characteristics were collected. Results: Overall, we observed a significant increase of IMT (0.03±0.10 mm, p=0.005) and plaques (+ 8%, p=0.035). The IMT progression rate was 0.027 mm/year (95% CI 0.007 - 0.046). Disease activity (DAS28-CRP) remained stable (2.68±1.01 vs 2.79±1.33, p=0.45). Anti-rheumatic, cardiovascular medications and the number of CV risk factors were substantially unchanged. In models of regression analysis sex, age, dyslipidemia, hypertension and use of corticosteroids were independently associated with the increase of IMT, whereas there were no confounding from use of biological therapies, seropositivity or disease duration. Patients with active disease (DAS28-CRP ≥2.6) had a significant increase in IMT (0.04±0.11 mm, p=0.009). Conversely, there was not a significant progression of patients in remission, who had also a lower prevalence of hypertension (40% vs 64%, p=0.027), dyslipidemia (43% vs 58%, p=0.044), and use of corticosteroids (37% vs 63%, p=0.007) and were receiving more frequently methotrexate (60% vs 40%, p=0.027). Conclusions: In patients with established and controlled RA, the progression of atherosclerosis is mainly driven by traditional CV risk factors than disease activity. In addition, a remission state is associated with a lower prevalence of CV risk factors, which in turn could account for a slower progression of atherosclerosis in these patients. This study provides evidence that even in RA patients who achieve good disease control the treatment of CV risk factors should be optimized. Disclosure of Interest: None declared